U.S. strategic solar photovoltaic-powered microgrid deployment for enhanced national security. (October 2017) - Prehoda, Emily W.; Schelly, Chelsea; Pearce, Joshua M.
Abstract: The U.S. electrical grid, the largest and most complex man-made system in the world, is highly vulnerable to three types of external threats: 1) natural disasters, 2) intentional physical attacks, and 3) cyber-attacks. The technical community has recommended hardening the grid to make it more resilient to attack by using distributed generation and microgrids. Solar photovoltaic (PV) systems are an ideal distributed generation technology to provide power for such microgrids. However, both the deployment velocity and the policy of how to implement such technical solutions have been given far less attention than would be normally considered adequate for a national security risk. To address this threat, this paper reviews the technical and economic viability of utilizing defense contracting for the beginning of a national transition to distributed generation in the U.S. First, the technical scale of electrical demand and the solar PV system necessary is analyzed in detail to meet the first level of strategic importance: the U.S. military. The results found that about 17 GW of PV would be needed to fortify the U.S. military domestically. The current domestic geographic deployment of microgrid installations in the critical U.S. defense infrastructure were reviewed and compared to historical grid failures and existing and planned PV installations to mitigate that risk. The results showed a minimal number of military bases have introduced solar PV systems, leaving large parts of the Department of Defense electrical infrastructure vulnerable to attack. To rectify this situation, the technical skills of the top 20 U.S. defense contractors is reviewed and analyzed for a potential contracting transition to grid fortification. Overall the results indicate that a fortified U.S. military grid made up of PV-powered microgrids is technically feasible, within current contractors skill sets and economically viable. Policy recommendations are made to accelerate U.S. military grid fortification.